Contraception utilization in women with pregestational diabetes - Walker, Shannon L.; Anguzu, Ronald; Egede, Leonard E.; Palatnik, Anna (The European Journal of Contraception & Reproductive Health Care, 2022)
Cross-sectional data on women aged 18–44 years from 2011 to 2017 National Survey of Family Growth (NSFG) was analysed. Maternal diabetes was defined as the presence of pre-gestational type 1 or type 2 diabetes. Bivariate and multiple logistic regression analyses were run to evaluate the association between the use of contraception and by contraception type: permanent, long-acting reversible contraception (LARC), other hormonal method, other non-hormonal method, and none, and maternal diabetes status, controlling for relevant covariates. Among the total study sample of 28,454, 1344 (4.7%) had pregestational diabetes. Unadjusted analysis showed women with a history of pregestational diabetes were more likely to use permanent contraception following pregnancy (58.0% vs. 38.7%, p < 0.001) or no contraception (27.2% vs. 24.5%, p < 0.001), but less likely to use LARC (3.4% vs. 11.7%, p < 0.001), other hormonal contraception (4.1% vs. 8.9%, p < 0.001), or other non-hormonal contraception (7.2% vs. 16.4%, p < 0.001). In adjusted analyses, permanent (aOR 1.62, 95% CI 0.72–2.26) remained significant, however the differences were no longer statistically significant: LARC (aOR 0.34, 95% CI 0.12–1.00); other hormonal (aOR 0.61, 95% CI 0.27–1.35); other non-hormonal (aOR 0.59, 95% CI 0.25–1.43); and None (aOR 1.11, 95% CI 0.65–1.89). In this analysis, we found that women with pregestational diabetes were more likely to use permanent contraception methods compared to women without pregestational diabetes; however over a quarter of women with pregestational diabetes did not use contraception between pregnancies.
Keywords: Pregestational diabetes; Contraception utilization; Women